2019
DOI: 10.1186/s13006-019-0227-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of breastfeeding in women with gestational diabetes in a University Hospital in Thailand

Abstract: Background Gestational diabetes mellitus (GDM), which is a medical complication that develops during pregnancy, is associated with several long-term health problems. Despite several benefits of exclusive breastfeeding (EBF), including reduction in long-term health problems in mothers with GDM, few studies have investigated breastfeeding in women with GDM and information in the Thai population is lacking. The aim of the study was to determine the prevalence of breastfeeding and the factors associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The interruption of breastfeeding has also been considered a complication among Southeast Asian women with GDM. These women have shorter breastfeeding durations than those without GDM in Thailand [84,85] and Vietnam [86]. The higher rates of obstetric and neonatal complications for both infants and GDM mothers [87], delays in the initiation of copious milk production [88], and suboptimal breastfeeding after hospital discharge [89] could be the reasons that lead to early breastfeeding cessation in this population.…”
Section: Gdm-related Complicationsmentioning
confidence: 99%
“…The interruption of breastfeeding has also been considered a complication among Southeast Asian women with GDM. These women have shorter breastfeeding durations than those without GDM in Thailand [84,85] and Vietnam [86]. The higher rates of obstetric and neonatal complications for both infants and GDM mothers [87], delays in the initiation of copious milk production [88], and suboptimal breastfeeding after hospital discharge [89] could be the reasons that lead to early breastfeeding cessation in this population.…”
Section: Gdm-related Complicationsmentioning
confidence: 99%
“…Nevertheless, breastfeeding duration in China is still far below the global nutrition targets (2). Several studies have reported that maternal antenatal intention to breastfeed is a strong predictor of actual duration of breastfeeding (3). Maternal postpartum intention could be much more associated with actual breastfeeding duration because of shorter time intervals and fewer impeding factors present during pregnancy, compared to maternal antenatal intention.…”
Section: What Are the Implications For Public Health Practice?mentioning
confidence: 99%
“…Maternal postpartum intention could be much more associated with actual breastfeeding duration because of shorter time intervals and fewer impeding factors present during pregnancy, compared to maternal antenatal intention. However, very little research has been done to determine if the maternal postpartum intention to breastfeed increases the duration of feeding in some mothers ( 4 ). This study was performed to examine the relationship between maternal postpartum intention and actual breastfeeding duration to provide data on the impact of extended breastfeeding duration.…”
mentioning
confidence: 99%
“…Despite all these facts, previous studies have shown that mothers with GDM have less intention to breastfeed than mothers without GDM and are less likely to continue breastfeeding [ 12 , 13 ]. Several barriers to adherence to breastfeeding have been identified, including lack of family support, lack of knowledge about breastfeeding benefits, maternal psychological factors, and smoking [ 11 , 14 , 15 , 16 , 17 , 18 ]. Cesarean section (elective or emergency), which is more prevalent among GDM mothers, has also been shown to play a significant role in delaying breastfeeding initiation, which then affects breastfeeding duration and continuation [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%